Nano/microparticle incorporated chitosan fibers as tissue engineering scaffolds - Yilgor, P. (2008)
[Excerpt] The aim of this study was to develop a bone tissue engineering scaffold with an inherent bone morphogenetic proteins BMP-2 and BMP-7 sequential delivery system. BMPs were encapsulated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and poly(lactic acid-co-glycolic acid) (PLGA) nano/microparticules which are then introduced to a chitosan matrix by two methods: embedding in the chitosan fibers and then forming the scaffold or by forming the chitosan scaffold and then introducing the nano/microparticules. [...]